2018
DOI: 10.2478/fhort-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Alternaria alternata – the main causal agent of disease symptoms in juniper, rose, yew and highbush blueberry in nurseries in southern Poland

Abstract: Symptoms of discoloration and necrosis of the leaves/needles and shoots of plants are an increasingly common phenomenon in nurseries. They necessitate the withdrawal of the affected plants from sale, which has significant economic consequences. In 2010-2011, observations were conducted of the health of shrubs in nurseries of the Małopolska province. Disease symptoms were mostly found in juniper (Juniperus horizontalis 'Wiltonii'), rose (ground-cover rose 'Star Profusion'), yew (Taxus × media 'Hillii') and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…Among 200 other Septoria species occurring in Poland, many cause spotting and necrosis of the herbaceous parts of plants. The infection of juniper by a fungal community similar to that found at the sewage treatment facility in Poznań was previously observed by Nadziakiewicz et al (2018).…”
Section: Discussionsupporting
confidence: 68%
“…Among 200 other Septoria species occurring in Poland, many cause spotting and necrosis of the herbaceous parts of plants. The infection of juniper by a fungal community similar to that found at the sewage treatment facility in Poznań was previously observed by Nadziakiewicz et al (2018).…”
Section: Discussionsupporting
confidence: 68%
“…Thus, these specific microorganisms from the TRz under DI that belong to taxa with known beneficial characteristics for plants, could be contributing to the tolerant phenotype, highlighting the metabolic bidirectionality of the holobiont system. Remarkably, some other fungal over-represented OTUs in the TRz under DI have also been associated with plant pathogenesis ( Zhang et al, 2005 ; Nadziakiewicz et al, 2018 ; Campos-Rivero et al, 2019 ; Jastrzêbska et al, 2020 ). Notwithstanding, since none of the plants in this study showed signs of any disease, these results emphasize that the development of an infectious disease depends on particular environmental factors and host-microbe interactions ( Bass et al, 2019 ), being some potential pathogens even plausibly relevant for the adaptation of plants to water deficit.…”
Section: Discussionmentioning
confidence: 99%
“…(Citrus, 2005). In addition, in V. corymbosum, species of Lasiodiplodia (Rodríguez-Gálvez et al, 2020), Nigrospora sphaerica (Wright et al, 2007), Alternaria alternata (Nadziakiewicz et al, 2018), Cladosporium tenuiussimum were identified as pathogens. (Lei et al, 2019), Stemphylium sp.…”
Section: Alternariamentioning
confidence: 99%